Severe Leptospira interrogans serovar Icterohaemorrhagiae infection with hepato‐renal‐pulmonary involvement treated with corticosteroids. Issue 5 (15th September 2014) - Schulze, Marco H.; Raschel, Heribert; Langen, Heinz‐Jakob; Stich, August; Tappe, Dennis
<x xml:space="preserve">Abstract</x> The traditional concept of immediate antibiotic treatment in suspected leptospirosis seems to be especially important for patients up to day 4 of clinical illness. As immune mechanisms probably play a crucial role in advanced leptospirosis with presumed pulmonary hemorrhages, patients might benefit from corticosteroids or other immunosuppressive agents beside antibiotics. <boxed-text content-type="graphic" id="ccr391-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>